2018
DOI: 10.1038/s41401-018-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

C11, a novel fibroblast growth factor receptor 1 (FGFR1) inhibitor, suppresses breast cancer metastasis and angiogenesis

Abstract: The fibroblast growth factor receptors (FGFRs) are increasingly considered attractive targets for therapeutic cancer intervention due to their roles in tumor metastasis and angiogenesis. Here, we identified a new selective FGFR inhibitor, C11, and assessed its antitumor activities. C11 was a selective FGFR1 inhibitor with an IC 50 of 19 nM among a panel of 20 tyrosine kinases. C11 inhibited cell proliferation in various tumors, particularly bladder cancer and breast cancer. C11 also inhibited breast cancer MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The inhibitory activity of compounds on growth was evaluated using the sulforhodamine B (SRB) colorimetric assay. Cells were seeded in 96-well plates, cultured overnight, and treated with a dilution series of test compounds for 72 h. Then, the SRB assay was performed according to standard protocols, as described previously [40].…”
Section: In Vitro Cell Proliferation Assaysmentioning
confidence: 99%
“…The inhibitory activity of compounds on growth was evaluated using the sulforhodamine B (SRB) colorimetric assay. Cells were seeded in 96-well plates, cultured overnight, and treated with a dilution series of test compounds for 72 h. Then, the SRB assay was performed according to standard protocols, as described previously [40].…”
Section: In Vitro Cell Proliferation Assaysmentioning
confidence: 99%
“…17,18 C11, an inhibitor of FGFR1, could curb angiogenesis and metastasis of BC. 34 Previous research revealed that FGFR1 promoted resistance to endocrine therapy and acted as a possible target for BC. 35 One report uncovered that FGFR1 expression was inhibited by miR-361-5p, which impeded BC cell invasion, proliferation, and glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR1 has been demonstrated as an oncogene in a series of cancers 17, 18 . C11, an inhibitor of FGFR1, could curb angiogenesis and metastasis of BC 34 . Previous research revealed that FGFR1 promoted resistance to endocrine therapy and acted as a possible target for BC 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our findings strongly identified that by suppressing the pRB-E2F1/CCNE2 and the RhoA/ROCK2 pathway, MFA attenuated the ability of migration and proliferation, attenuated the expression of fibrosis-related proteins in HCFs, and improved the cardiac function in MI mice meanwhile. But interestingly, we found that when mice injected by MFA without MI, the expression of α-SMA was significantly decreased, from other reports we knew that ferulic acid (FA), the ramification of MFA, suppressed the expression of fibroblast growth factor receptor 1 (FGFR1), and hence suppressed the angiogenesis and α-SMA expression (Yang et al, 2015;Chen et al, 2019). Although the effect of MFA on FGFR1 was not reported, we assumed that it might play the same role as FA.…”
Section: Discussionmentioning
confidence: 80%